Clinical Utility of MMP-9 Expression in Oral Malignant and Premalignant Lesions - Shafiq, Fiza (International Journal of Pathology, 2022)
Introduction: The main histological form of oral cancer is oral squamous cell carcinoma (OSCC) which predominantly arises from oral potentially malignant lesions. Matrix metalloproteinases-9 (MMP-9) can degrade different elements of the ECM and basement membrane. In the present study, MMP-9 expression was assessed in tissue samples among cases of oral squamous cell carcinoma, oral potentially malignant disorders (OPMDs) and healthy individuals to assess its important role in OSCC and OPMDs. Objective: This study aims to assess the immunohistochemical expression of MMP-9 in tissue samples of diagnosed cases of oral squamous cell carcinoma, OPMDs, and normal oral mucosa. Material and Methods: A total of 60 histologically diagnosed cases of OSCC (n=25), OPMDs (n=25), and Healthy individuals (n=10) as control were included. Immunohistochemical staining was performed for all cases. Results were analyzed using SPSS version 20. Results: Increased expression of MMP-9 was observed in OSCC cases (n=23/25; 92%) as compared to OPMDs and healthy individuals. Statistically, a significant relation was observed while comparing the grade of staining intensity and MMP-9 expression among OSCC cases (p=0.001) and OPMD cases (p= ≤ 0.01). Conclusion: Increased expression of MMP-9 was observed in OSCC as compared to OPMDs and healthy individuals. Evaluation of MMP-9 could be of clinical importance in OSCC and can be used as a diagnostic marker of OSCC and OPMDs